PRINCIPLES OF LEGAL RIGHTS IN OPERATIONAL POWERS OF THE STATE BORDER GUARD - Gaveika, Artūrs (Border Security and Management, 2018)
The current Border Guard Law, which came into force in 1998, from jurisdictional perspective and in terms of content and is out-dated since it only reflects some of the legal principles that the State Border Guard must apply as a national regulatory authority in its activities. The novelty of the article is that the author proposes the development of the Border Guard Law in a new version, which would include specific principles of the Border Guard, in close conjunction with the authority's powers, rights and responsibilities.The aim of the study is to develop and propose a number of special Border Guard operational principles for their inclusion into the regulatory framework of the Border Guard. The research tasks are to investigate the current normative regulations, legal practices, the conclusions of Latvian and foreign law researchers using analytical, historical and comparative methods.The principles of law are reflected in many regulatory enactments and they must be observed and applied to each state administration institution, including the State Border Guard, and their repetition is not required by the special laws binding on the State Border Guard. The application of the principles of law is closely related to the fulfilment of the tasks, rights and obligations assigned to the State Border Guard, therefore the author seeks to investigate their development in historical dynamics.The main achievement of the research is that the author has tried to define the main special principles of the State Border Guard.